La teoría económica espacial y los principios de la política económica regional - Vito, Francesco (1960)
After propounding the denominations of backward, subdeveloped and depressed economy, respectively, the author outlines broadly the evolution of spaces studies, scientific principles to be applied for the delimitation of the region, points out factors to be considered according to the case and circumstances, in order to determine regional inequalities and the principles of regional policy applicable for the possible solution of each case, taking as reference zones those of N.W. S.W. of France (depressed zone) and south of Italy (underdeveloped zone).